Intentions of Halal Meat Exportation among Butchers in the Kano Abattoir Market: Empirical Insights from Nigeria - Muhammad Mukhtar Idris; Muhammad Aminu Isa; Sagir Muhammad Sulaiman (Sekolah Tinggi Agama islam Negeri Majene, 2026)
The exportation of halal meat represents a strategic business opportunity for Nigeria, yet the potential contribution of local butchers to the global halal market remains largely underutilised. This study examines the determinants of butchers’ intention to export halal meat in the Kano abattoir market, focusing on the roles of perceived benefits, organisational commitment, and government support. Using a descriptive survey design, the study collected cross‑sectional data through self‑administered questionnaires and analysed the responses using Structural Equation Modelling (SEM). The findings reveal that perceived benefits and government support exert significant positive influences on butchers’ export intentions, whereas organisational commitment shows no significant effect. These results underline the importance of strengthening awareness of export-related benefits and enhancing government-led support mechanisms to stimulate participation in halal meat export activities. The study highlights the need for targeted sensitisation programs, strategic financial incentives, trade promotion initiatives, and improvements in organisational practices to cultivate a more export-oriented mindset among butchers in the region.